39 Kids on the Block The Green Ghost of Appleville #1 - Jean Marzollo (U.S.A, 1989)
Fizz Eddie has already seen the much-talked-about Green Ghost, said to inhabit the eerie farmhouse on the block, and the rest of the kids fearfully question the spirit's existence.
Keywords: Fiction -- Fiction